UPAYA POLRI DALAM MENANGGULANGI TINDAK PIDANA PENCURIAN KENDARAAN BERMOTOR DI WILAYAH HUKUM POLSEK GALIS KABUPATEN BANGKALAN MADURA JAWA TIMUR - Muafi; Andi Nurhidayah (Constitutum: Jurnal Ilmiah Hukum, 2024)
The crime rate of motor vehicle theft continues to increase along with the increasing economic burden and increasing unemployment rates. This has a significant impact on community welfare. This study discusses the factors causing motor vehicle theft and the efforts made by the Indonesian National Police (Polri) in overcoming motor vehicle theft in the jurisdiction of the Polsek Galis, Bangkalan Regency, Madura, East Java. The research method used is normative juridical combined with empirical juridical. The results of the study indicate that the factors causing motor vehicle theft in the Polsek Galis include economic difficulties, sociological factors (social interactions, lack of parental supervision of teenagers), environmental factors, and lack of vigilance and negligence of residents. The efforts made by the Polri in overcoming motor vehicle theft in the jurisdiction of the Polsek Galis show that the approach taken is more repressive. In addition, in handling motor vehicle theft cases in particular, the process carried out is to uncover the theft case, report it, then hold a meeting for evaluation. This allows for action to be taken to reduce and uncover motor vehicle theft. However, there are still challenges in practice, such as the lack of facilities and human resources, which are very important for the effectiveness of law enforcement.